Growth is good, but is not enough to improve nutrition - Ecker, Olivier; Breisinger, Clemens; Pauw, Karl (International Food Policy Research Institute, 2011)
While it is generally agreed that growth is a necessary precondition for reducing poverty, relatively little is known about the relationship between economic growth and nutrition and, hence, how economic policies can be leveraged to improve nutrition. This brief argues that growth is good, but is not enough to improve nutrition. During the early stages of development, growth helps reduce the prevalence of calorie deficiency, and, in most countries, agricultural growth plays a key role. But malnutrition becomes less responsive to growth as its prevalence rate declines, so economic diversification into the manufacturing and service sectors becomes necessary to leverage further reductions in malnutrition, especially as people migrate into urban areas. Nevertheless, growth—whether driven by the agriculture or nonagriculture sectors—is insufficient to address child malnutrition and reduce micronutrient malnutrition in all their dimensions. Strategic investments and special programs are needed in the complementary sectors of health and education as well.